Crystal structure of 1,2-bis(4,5-dinitro-1H-imidazol-1-yl)ethane, C8H6N8O8 - Yong Wang; Bingheng Wu; Jun Yuan; Duanlin Cao; Jianlong Wang; Lizhen Chen (Zeitschrift für Kristallographie - New Crystal Structures)
C8H6N8O8, orthorhombic, P212121 (no. 19), a = 6.7563(9) Å, b = 7.2512(12) Å, c = 25.884(3) Å, V = 1268.1(3) Å3, β = 90°, Z = 4, R gt(F) = 0.0473, wR ref(F 2) = 0.1170, T = 170 K.